The Continuity of the Meter: The Redefinition of the Meter and the Speed Of Visible Light - Jennings, D. A. (J Res Natl Bur Stand (1977), 1987)
The product of the frequency and wavelength of the i(th) hyperfine component of the 11-5, R(127) transition of (127)I(2) yields a value for the speed of visible red light. This value of c, the most accurate ever measured for visible light, agrees with the value defined in the redefinition of the meter within the 3σ error limits of the krypton length standard.